+0  
 
-1
318
4
avatar+104 

Match each expression to its equivalent expression with the rational denominators.

 

Tiles

\(^1/_{\sqrt[4]{3x^3y^5}}\)

\(^3/_{\sqrt[4]{27x^{11}y^{13}}}\)

\(^2/_{\sqrt[6]{2x^7y^5}}\)

\(^4/_{\sqrt[6]{32x^5y^9}}\)

 

Pairs

\(^{2\sqrt[6]{2xy^3}}/_{xy^2}\to\)

\(^{\sqrt[4]{27xy^3}}/_{3xy^2}\to\)

\(^{\sqrt[4]{3xy^3}}/_{x^3y^4}\to\)

\(^{\sqrt[6]{32x^5y}}/_{x^2y}\to\)

SpaceModo  Jan 19, 2018
 #1
avatar+94183 
+2

Hi SpaceModo,

 

I'll do one of them.

 

\(\frac{{2\sqrt[6]{2xy^3}}}{_{xy^2}}\\ =\frac{{2\sqrt[6]{2xy^3}}}{\sqrt[6]{x^6y^{12}}}\\ =\frac{{2\sqrt[6]{2}}}{\sqrt[6]{x^5y^{9}}}\times\frac{2^{5/6}}{2^{5/6}}\\ =\frac{{2*2}}{\sqrt[6]{x^5y^{9}}}\times\frac{1}{(2^5)^{1/6}}\\ =\frac{{4}}{\sqrt[6]{32x^5y^{9}}}\\ \)

 

 

That is one done, now you can copy the technique and try matching up the others.

If you do not understand this one just ask and see if you can specify what line is giving you trouble :)

Melody  Jan 20, 2018
 #4
avatar+104 
0

\begin{align*}...
{^4/_{\sqrt[6]{32x^5y^9}}}&\stackrel{?}{=}{^{2\sqrt[6]{2xy^3}}/_{xy^2}}\\
{^4/_{\sqrt[6]{32x^5y^9}}}&\stackrel{?}{=}{^{2\sqrt[6]{2xy^3}}/_{\sqrt[6]{32x^5y^9}}}\\
{^4/_{\sqrt[6]{32x^5y^9}}}&\stackrel{?}{=}{^{2\sqrt[6]{2}}/_{\sqrt[6]{x^5y^9}}}\times{^{2^{^{^5}/_6}}/_{2^{^5/_6}}}\\
{^4/_{\sqrt[6]{32x^5y^9}}}&\stackrel{?}{=}{^{2\times2}/_{\sqrt[6]{x^5y^9}}}\times{^1/_{(2^5)^{^1/_6}}}\\
{^4/_{\sqrt[6]{32x^5y^9}}}&\stackrel{\checkmark}{=}{^4/_{\sqrt[6]{32x^5y^9}}}
\end{align*}

\(\begin{align*} {^4/_{\sqrt[6]{32x^5y^9}}}&\stackrel{?}{=}{^{2\sqrt[6]{2xy^3}}/_{xy^2}}\\ {^4/_{\sqrt[6]{32x^5y^9}}}&\stackrel{?}{=}{^{2\sqrt[6]{2xy^3}}/_{\sqrt[6]{32x^5y^9}}}\\ {^4/_{\sqrt[6]{32x^5y^9}}}&\stackrel{?}{=}{^{2\sqrt[6]{2}}/_{\sqrt[6]{x^5y^9}}}\times{^{2^{^5/_6}}/_{2^{^5/_6}}}\\ {^4/_{\sqrt[6]{32x^5y^9}}}&\stackrel{?}{=}{^{2\times2}/_{\sqrt[6]{x^5y^9}}}\times{^1/_{(2^5)^{^1/_6}}}\\ {^4/_{\sqrt[6]{32x^5y^9}}}&\stackrel{\checkmark}{=}{^4/_{\sqrt[6]{32x^5y^9}}} \end{align*}\)

 

][   |) ()   \/ ≡ R y   ( () |\/| P |_ ≡ ><   |\/| /-\ T |-|   ( () |) | |\| G!

However, thank you very much for the help I needed!

SpaceModo  Jan 22, 2018
 #2
avatar+92856 
+1

4√[ 27xy^3] / [ 3xy^2]      writing this in an exponential fashion, we have

 

[ (3^3)^(1/4) * x^(1/4)  * y^(3/4) ]  /  [  3xy^2]  =

 

[( 3^3)(1/4)  * x^(1/4) * y^(3/4)  /  [  (3^(4/4) * x^(4/4) * y^(8/4)  ]

 

[ 3^(3/4)  * x^(1/4)  * y^(3/4) ]  /  [  3^(4/4) * x^(4/4) * y^(8/4)  ]  =

 

{ Using   a^m / a^n  =   a^(m - n)  }

 

1  /  [ 3^(1/4) * x^(3/4) * y^(5/4) ]   write back in radical form

 

1 / 4√ [ 3x3y5 ]

 

 

cool cool cool

CPhill  Jan 20, 2018
 #3
avatar+92856 
+1

4√[ 3xy^3 ]  /  [ x^3y^4 ]  =

 

[  3^(1/4) * x^(1/4)  * y^(3/4) ] / [ x^(12/4) *y^(16/4) ]  =

 

3^(1/4)  / [  x^(11/4) * y^(13/4) ]  =

 

Multiply  top/bottom  by  3^(3/4)  =

 

[ 3^(1/4) * 3^(3/4)] /  [ x^(11/4) * y^(13/4)  * 3^(3/4) ]  =

 

3 / [  x^(11/4) * y^(13/4) * 27^(1/4)  ]

 

Write back in radical form

 

3 / 4√ [  27  x11 y13 ]

 

 

 

cool cool cool

CPhill  Jan 20, 2018

21 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.